Care transfer: discharge process of users in a psychosocial attention center - Ariane da Cruz Guedes; Agnes Olschowsky; Luciane Prado Kantorski; Milena Hohmann Antonacci (Universidade Federal de Goias, 2017)
The discharge in mental health services has a psychosocial rehabilitation connotation and articulation with network devices to promote continued attention in the territory. The aim was to assess the discharge process of users in Psychosocial Attention Centers (CAPS). A qualitative and evaluative study, based on the Fourth Generation Assessment. It was conducted in a CAPS II in Santa Catarina, with 17 workers, 14 family members and, five users, in 2014. We used the Constant Comparative Method to analyze the data. We comprehended the discharge process as an important psychosocial rehabilitation process, promoting care in the life territory of users. Our study question of admissions being chronic in CAPS, as services, should not keep accompanying users for long periods of time, but to be transitory, allowing care to get stronger in other points of the network, narrowing links with the primary attention and with the other social equipment from the territory.